Mengarifi Orientalisme: Meretas Jalan Ke Arah Integrasi Epistemologi Studi Islam - Afrizal Afrizal (Universitas Islam Negeri Mataram, 2007)
Islamic studies taken by orientalists are often suspected as having hidden agenda. Main indicator of such agenda, according to Edward W. Said, is their biased works on Islam. Regardless to its negative side, honestly to say, orientalism has contributed important aspects in Islamic studies in terms of establishing approaches and methodologies, and creating new fields as branches of Islamic studies. Besides, they do give significant role in preservation and maintenance of Muslim intellectual heritage (turâts) such as manuscripts. In the context of Islamic studies in IAIN, the raise of attention to orientalism studies will gradually balance the hegemony of its textual tradition based on Arabs and Persian bayânî and ‘irfânî epistemologies with Western sciences that are compatible with burhânî epistemology. The balance hopefully would be a kind of Islamic studies that more historical and inclusive in nature, analyzing any problem not only from religious but scientific perspective as well.